محا ضات ف اء 1 )ميكانيك النقطة المادية( - نسيمة, مفتاح (university of eloued جامعة الوادي, 2023)
هذه المحاضرات بعنوان الفيزياء 1 )ميكانيك النقطة المادية( هي أداة بيداغوجية موجهة لطلبة السنة أولى جامعي لعلوم المادة ) SM ( نظام ل-م-د. و أعد محتوى هذه الدروس وفقا للبرنامج الرسمي و تم تقديمها بأسلوب بسيط يتيح للطالب سهولة الفهم و إستعاب المسائل المتعلقة بحركة الأجسام المادية عموما. وهي مقسمة لستة فصول، الفصل الأول بعنوان تذكرة رياضية و ذلك لتذكير الطالب ببعض الوسائل الرياضية التي تساعده في التعامل مع المسائل الفيزيائية، و الفصل الثاني يتناول كل ما يتعلق بالتحليل الشعاعي، ثم يليه فصل يتناول دراسة حركة الاجسام المادية و ذلك في مختلف المعالم، ثم فصل يتضمن دراسة الحركة النسبية، يليه فصل يتناول دراسة تحريك الاجسام المادية و في الاخر فصل حول الطاقة والعمل. و كل هاته الفصول مدعمة بمخططات توضيحية و أمثلة تطبيقية. These lectures, entitled Physics 1 (Physical Point Mechanics), are a pedagogical tool directed at first-year university students in material sciences (SM), L-M-D system. The content of these lessons was prepared in accordance with the official program and was presented in a simple manner that allows the student to easily understand and comprehend issues related to the movement of physical bodies in general. It is divided into six chapters. The first chapter is entitled Mathematical Reminder, in order to remind the student of some mathematical methods that help him in dealing with physics problems. The second chapter deals with everything related to radiological analysis, then it is followed by a chapter that deals with the study of the movement of physical bodies in various parameters. Then A chapter includes the study of relative motion, followed by a chapter that deals with the study of moving physical bodies, and in the end a chapter on energy and work. All of these chapters are supported by illustrative diagrams and practical exa
محاضرات في الفيزياءلطلبة سنة الأولى almd